Comparison of Conbercept with Ranibizumab for the Treatment of Macular Edema Secondary to Branch Retinal Vein Occlusion. (3rd August 2017) - Li, Fengjiao; Sun, Ming; Guo, Jianlian; Ma, Aihua; Zhao, Bojun
ABSTRACT: Purpose : To confirm the therapeutic efficacy of conbercept for the treatment of macular edema (ME) secondary to branch retinal vein occlusion (BRVO). Methods : In this prospective, randomized, and comparative study, patients were randomized and divided into conbercept (n = 18) and ranibizumab (n = 17) groups. After an initial intravitreal injection of either conbercept or ranibizumab, a pro re nata (PRN) strategy was adopted based on loss of visual acuity (VA) or increase in central macular thickness (CMT). Results : All patients were followed for ≥6 months. Baseline best-corrected visual acuities (BCVAs) were 0.67 ± 0.37 and 0.511 ± 0.23 logMAR in the conbercept and ranibizumab groups, respectively ( p = 0.087, t-test ). Baseline CMTs were 512.5 ± 115.22 and 491.23 ± 114.72 µm in the conbercept and ranibizumab groups, respectively ( p = 0.993, t-test ). Significant improvements in BCVA and reduction of CMT were observed in both groups at each follow-up visit and compared to baseline values ( p < 0.05, t -test). No significant differences in improvement of BCVA (p > 0.05, t-test) or reduction of CMT ( p > 0.05, t-test ) were noted in either group. Mean numbers of injections were 2.28 ± 0.96 and 2.65 ± 1.17 for the conbercept and ranibizumab groups, respectively ( p = 0.478, t-test ), with no statistically significant differences between the two groups. Conclusion : Intravitreal injection of conbercept is shown to be safe and effective for the treatment of ME secondary to BRVO, based on 6-month follow-up data.